The effect of emotional intelligence, competency and financial compensation on performance of employee with job satisfaction - Edi Sugiono; Siti Nurhasanah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This research aims to understand the impact of emotional intelligence, ability, and economic compensation on employee performance through the job satisfaction of Detikcom employees. In this study, the sample used was 110 respondents using simple random sampling techniques. The results show that the three variables of emotional intelligence, competence and economic compensation have significant positive effects on job satisfaction. Emotional intelligence and ability variables have a positive and significant impact on employee performance. Financial compensation variables have a positive but insignificant effect on employee performance. Variables such as emotional intelligence, competence, and economic compensation have a positive and significant impact on employee performance through job satisfaction. In addition, variable job satisfaction has a positive and significant impact on employee performance.